Dukungan Peer Group Terhadap Kepatuhan Konsumsi Minum Obat Tablet Tambah Darah Pada Remaja Putri Di SMA N 1 Banguntapan Tahun 2020 - Indrayanti; Defintasari Sri Raharjo (Journal of Health (JoH), 2021)
Anemia is a problem that occurs throughout the world, especially in female teenagers. The high number of anemia makes the Government to make a program of providing iron tablet. Factors of adherence to taking medication consist of internal and external factors. One of the external factors is peer support. Peer Group Support is one way to improve female teenagers adherence in taking iron tablet medication. Statistical test results show is significant relationship between peer group support for adherence to taking tablets blood in adolescent girls (p value <alpha = 0,000 <0.05) with a correlation of 0.508, namely moderate closeness. The conclusion of this research there is a relationship of Peer Group Support and iron tablet medication adherence in female teenagers of SMA N 1 Banguntapan in 2020